The Predictive ability of Mindfullness in Burnout among inclusive schools Teachers in Alkarak Governorate - Alkhtatnah, Asmaa Abdelwahab; Ibrahim, Mikail (Journal of Educational and Psychological Sciences, 2025)
This study aimed to reveal the level of burnout and the mindfulness among the teachers of the inclusive schools in Alkarak Governorate,and to identify the extent to which Mindfulness contribute to predicting the burnout among the teachers. The study sample consisted of 320 teachers(107 male and 213 female).To achieve the objectives of the study, This study used Maslach scale of burnout,and the Five Facet Mindfulness Questionnaire (FFMQ) scale of mindfulness were used, and the descriptive and predictive curriculum was used also because of its suitability to the study’s goals. The study found the following results:1- the level of burnout and the mindfulness were modrate among the study sample. 2-There is a significant negative relationship between the burnout and the mindfulness.3-The study revealed the predictive ability of mindfulness of burnout , Stepwise Multiple Regression analysis showed that two of mindfulness dimensions ;act with awareness and non-react  have a predictive  ability of burnout , the study proves that the act with awareness is the most predicting of burnout, and the non-react comes as the next factor. The study concludes that integrating mindfulness practices into teacher professional development programs can serve as an effective strategy to mitigate.
Keywords: Burnout; Mindfulness; inclusive; inclusive schools